The Changing Face of Atherosclerosis - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Statins have been used for around three decades as the primary way to lower cholesterol and reduce the risk of atherosclerosis, but in some groups, statin resistance is common, and the danger of atherosclerosis is still high.CONTENT: Atherosclerosis was once believed to be caused by cholesterol and thrombotic material passively accumulating in the walls of arteries. However, current knowledge shows that the immune cells and inflammatory processes are essential in the formation, progression, and consequences of atherosclerotic lesions, characterized by a persistent inflammatory response, including thrombotic complications. Study of genetic, creating risk score for atherosclerosis, add more information to create more new therapies targeting low density lipoprotein cholesterol (LDL-C) receptor, and shows prospect.SUMMARY: Over time, atherosclerosis theories and treatment strategies have changed. While statins were widely used, they have now been supplanted by alternative options like the proprotein convertase subtilisin/kexin type 9 (PSCK9) inhibitor that manage atherosclerosis more effectively and comprehensive.KEYWORDS: atherosclerosis, cholesterol, inflammation, immune system, metabolism